Building type basics for performing arts facilities - Hardy, Hugh (John Wiley & Sons, Inc., 2006)
This Building Type Basics book provides an accessible guide to the essentials of designing these specialized environments—including the underlying issues of financing, feasibility, and the diverse roles of the design and construction team, sponsor, banks, impresario, and manager. Complete with a wealth of descriptive floor plans, diagrams, photographs, and case studies, it features need-to-know information on design including such technical topics as lighting, acoustics, and materials.